Electronic, Magnetic and Structural Properties of the Spin Liquid Candidate BaTi1/2Mn1/2O3 - Cantarino, Marli dos Reis (2019)
This work presents macroscopic and microscopic experiments of the disordered hexagonal double perovskite BaTi1/2Mn1/2O3, in order to characterize its electronic, magnetic and structural properties to support the possibility that this system hosts a spin liquid phase. Such assumption is based on the absence of a transition to a magnetically ordered phase in the magnetic and thermodynamic measurements, which points to a strong magnetic frustration in this material. In addition, it is observed the formation of a correlated spin state. To characterize this correlation, we resorted to Muon Spin Resonance (µSR) experiments to measure the low temperature spin dynamics. The zero field µSR relaxation regime displays dynamic magnetism down to T = 0.019 K and longitudinal field experiments support as well that dynamic magnetism persists at low temperatures, a behavior expected for a spin liquid system. The magnetic behavior of BaTi1/2Mn1/2O3 consists in the high temperature physics being dominated by the presence of magnetic trimers, magnetic dimers, and orphan spins. At lower temperatures, the effective magnetic degrees of freedom, composed by orphan spins and magnetic trimers, are correlated but no phase transition is detected down to T = 0.1 K, despite the effective exchange couplings between magnetic trimers and orphan spins being -8.5 K, resulting in a magnetic frustration parameter of at least 85. The possibility that disorder is responsible for the spin liquid ground state is discussed, however, other scenarios are not totally discarded. For example, the possibility that the measured state is not the true ground state, which could lie at even lowers temperatures or the possible formation of a spin glass state. This work raises questions that are not easy to answer. Ultimately, the growth of a single crystal is necessary to continue the characterization of BaTi1/2Mn1/2O3. Besides, theoretical and experimental developments in this field of research are needed to find a more direct and conclusive way to characterize the magnetic phases in this complex material.